2022
DOI: 10.29122/jtl.v23i1.4949
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Potensi Pencemaran Air Tanah Bebas di Lereng Kaki Koluvial dan Dataran Aluvial Daerah Aliran Sungai Pesing Menggunakan Integrasi Metode GOD dan SIG Berbasis Web

Abstract: Agricultural, livestock, and domestic activities in the alluvial plains and the colluvial footslopes of the Pesing watershed have the potential to reduce groundwater quality in an unconfined aquifer. Environmental characteristics need to be identified spatially to determine the potential for groundwater contamination. The latest mapping technology also needs to be identified to determine its ability to disseminate information on potential groundwater pollution. The research was conducted to determine the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The fluctuations in E. coli levels are attributed to human domestic activities and livestock land use. Additionally, excessive use of manure in agricultural areas may also result in high levels of E. coli bacteria due to livestock waste infiltrating the soil and contaminating the groundwater (Sejati & Saputra, 2022). In addition to the aforementioned factors, high levels of E. coli bacteria in the area are also attributed to the proximity of septic tanks in residential areas to groundwater sources.…”
Section: Groundwater Condition Based On Biological Parametermentioning
confidence: 99%
See 2 more Smart Citations
“…The fluctuations in E. coli levels are attributed to human domestic activities and livestock land use. Additionally, excessive use of manure in agricultural areas may also result in high levels of E. coli bacteria due to livestock waste infiltrating the soil and contaminating the groundwater (Sejati & Saputra, 2022). In addition to the aforementioned factors, high levels of E. coli bacteria in the area are also attributed to the proximity of septic tanks in residential areas to groundwater sources.…”
Section: Groundwater Condition Based On Biological Parametermentioning
confidence: 99%
“…The gathered data suggested that the research area contains horizontally and vertically distributed sand material in both zones, with excellent permeability. Previous studies have assigned significant importance to sand material as a variable in modeling groundwater pollution (Adji et al, 2013;Sejati & Saputra, 2022;Sejati, 2020;Vrba & Zoporozec, 1994). The sand with high permeability facilitates the movement of pollutants towards the groundwater-saturated zone.…”
Section: Groundwater Quality Based On Water Quality Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Groundwater is a natural resource with disparity across the different regions throughout time. Groundwater quantity is significantly impacted by geological features, changes in land use, and climate change (Santosa & Adji, 2014;Sejati & Saputra, 2022). People's dependency on groundwater to fulfilling their needs also affects the groundwater dynamic (Sejati, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Such as household activities, the hotel industry, hospitals, workshops, mining, and agricultural activities. All of these activities will produce waste or rubbish which, if not managed properly, can hurt the environment one of which is groundwater pollution (Rahman, 2008;SEJATI & SAPUTRA, 2022).…”
Section: Introductionmentioning
confidence: 99%